Perspectives on climate change and adaptation in Fijian villages contemplating relocation - Yoshida, Yuki; Sioen, Giles B.; Metuisela, Gauna; Crichton, Richard (Frontiers in Climate, 2025)
Planned relocation is increasingly recognized as a necessary response to escalating climate risks, yet little is known about how such decisions unfold at the community level. Drawing on dialogs and field visits at seven iTaukei (Indigenous Fijian) villages across Fiji, this report examines how communities are experiencing and responding to climate-related challenges. Findings reveal cascading impacts—including flooding, land loss, disrupted livelihoods, and psychological stress—that have prompted a range of adaptation strategies, from in-situ adjustments to full or partial relocation, with mixed outcomes. Despite growing pressures, most communities expressed a strong, culturally grounded preference to remain in place. Challenges in reaching consensus and securing funding reflect the complexity of relocation processes. Moreover, traditional governance structures do not always ensure equal participation, highlighting the importance of attending to intra-community dynamics. To minimize loss and damage while ensuring agency and resilience of frontline communities, climate mobility frameworks will need to support anticipatory planning, uphold community agency, and recognize immobility as a legitimate and often preferred option.